2013
DOI: 10.1175/jcli-d-13-00440.1
|View full text |Cite
|
Sign up to set email alerts
|

Weakening Trend of the Tropical Easterly Jet Stream of the Boreal Summer Monsoon Season 1950–2009

Abstract: Recent research has reported that the tropical easterly jet stream (TEJ) of the boreal summer monsoon season is weakening. The analysis herein using 60 yr ) of data reveals that this weakening of the TEJ is due to the decreasing trend in the upper tropospheric meridional temperature gradient over the area covered by the TEJ. During this period, the upper troposphere over the equatorial Indian Ocean has warmed due to enhanced deep moist convection associated with the rapid warming of the equatorial Indian Ocean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 16 publications
2
31
0
Order By: Relevance
“…However, some previous studies have questioned the direct role of tropospheric temperature gradient in changing the monsoon winds [Lindzen and Hou, 1988;Bordoni and Schneider, 2008;Molnar et al, 2010], and it has been shown that a weakened regional Hadley circulation with a southward displaced ascending branch can itself lead to a decrease in monsoon winds without invoking changes in the meridional upper tropospheric temperature gradient and hence a weakened wind shear [Lindzen and Hou, 1988;Bordoni and Schneider, 2008]. In contrast to these studies, Abish et al [2013] have shown that the rapid Indian Ocean warming and the associated convection have warmed the upper troposphere over the central equatorial Indian Ocean and thereby weakened the meridional tropospheric temperature gradient and this has reduced the monsoon winds through the thermal wind balance. However, our discussion on the Indian Ocean warming and associated changes in the regional Hadley circulation and its impact on the MISO propagation are not dependent on any of these arguments.…”
Section: Mechanismsmentioning
confidence: 98%
See 1 more Smart Citation
“…However, some previous studies have questioned the direct role of tropospheric temperature gradient in changing the monsoon winds [Lindzen and Hou, 1988;Bordoni and Schneider, 2008;Molnar et al, 2010], and it has been shown that a weakened regional Hadley circulation with a southward displaced ascending branch can itself lead to a decrease in monsoon winds without invoking changes in the meridional upper tropospheric temperature gradient and hence a weakened wind shear [Lindzen and Hou, 1988;Bordoni and Schneider, 2008]. In contrast to these studies, Abish et al [2013] have shown that the rapid Indian Ocean warming and the associated convection have warmed the upper troposphere over the central equatorial Indian Ocean and thereby weakened the meridional tropospheric temperature gradient and this has reduced the monsoon winds through the thermal wind balance. However, our discussion on the Indian Ocean warming and associated changes in the regional Hadley circulation and its impact on the MISO propagation are not dependent on any of these arguments.…”
Section: Mechanismsmentioning
confidence: 98%
“…In contrast to these studies, Abish et al . [] have shown that the rapid Indian Ocean warming and the associated convection have warmed the upper troposphere over the central equatorial Indian Ocean and thereby weakened the meridional tropospheric temperature gradient and this has reduced the monsoon winds through the thermal wind balance. However, our discussion on the Indian Ocean warming and associated changes in the regional Hadley circulation and its impact on the MISO propagation are not dependent on any of these arguments.…”
Section: The Agcm Experimentsmentioning
confidence: 99%
“…Another factor could be the weakening of the tropical easterly jet (Koteswaram, ) in the 20th century found by Abish et al . (), resulting in stronger mean zonal winds.…”
Section: Discussionmentioning
confidence: 99%
“…However, Huang et al (2001) suggested that this increase may be due to an intensification of El Niño events or Madden-Julian Oscillations, which would result in stronger westerly winds in the tropical upper troposphere (Lee, 1999). Another factor could be the weakening of the tropical easterly jet (Koteswaram, 1958) in the 20th century found by Abish et al (2013), resulting in stronger mean zonal winds.…”
Section: Trend Analysismentioning
confidence: 99%
“…For example, studies have shown a weakening of MLLJ in recent decades (Joseph and Simon, 2005;Krishnan et al, 2013). Recent studies show a poleward shift in MLLJ (Sandeep and Ajayamohan, 2015), weakening of TEJ (Abish et al, 2013) and strengthening of subtropical jet stream (Abish et al, 2015). The Intergovernmental Panel on Climate Change (IPCC) (2007) on the basis of results from general circulation models has shown that daily heavy rainfall events in many regions around the globe show an increasing tendency.…”
Section: Introductionmentioning
confidence: 99%